1997
DOI: 10.1128/mcb.17.10.6114
|View full text |Cite
|
Sign up to set email alerts
|

Rnr4p, a Novel Ribonucleotide Reductase Small-Subunit Protein

Abstract: Ribonucleotide reductases catalyze the formation of deoxyribonucleotides by the reduction of the corresponding ribonucleotides. Eukaryotic ribonucleotide reductases are ␣ 2 ␤ 2 tetramers; each of the larger, ␣ subunits possesses binding sites for substrate and allosteric effectors, and each of the smaller, ␤ subunits contains a binuclear iron complex. The iron complex interacts with a specific tyrosine residue to form a tyrosyl free radical which is essential for activity. Previous work has identified two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 30 publications
4
125
0
1
Order By: Relevance
“…This organism possesses no deoxynucleoside kinase activities, and thus, dNTP synthesis is entirely dependent on RNR (72). In S. cerevisiae, the levels of the subunits are controlled transcriptionally and the level of mRNA of the α subunit is increased during the S-phase of the cell cycle during normal growth, while the levels of mRNA for the β and β′ subunits remain largely unchanged (22,25,27,31). We have recently shown that the mRNA levels are correlated with the protein levels (D. L. Perlstein, M. Huang, and J. Stubbe, unpublished results).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This organism possesses no deoxynucleoside kinase activities, and thus, dNTP synthesis is entirely dependent on RNR (72). In S. cerevisiae, the levels of the subunits are controlled transcriptionally and the level of mRNA of the α subunit is increased during the S-phase of the cell cycle during normal growth, while the levels of mRNA for the β and β′ subunits remain largely unchanged (22,25,27,31). We have recently shown that the mRNA levels are correlated with the protein levels (D. L. Perlstein, M. Huang, and J. Stubbe, unpublished results).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a Tyr-to-Phe substitution at the Tyr designed to be oxidized has no effect on β′ function in vivo (27). Thus, ββ′ can maximally contain a single diferric-Y • cofactor located in the active site of β.…”
mentioning
confidence: 99%
“…As the RNR enzyme complex is the molecular target of HU, we reasoned that genetic impairment Journal of Cell Science 119 (24) of RNR activity would hamper growth of the ccr4⌬ strain. Although RNR1 and RNR4 are essential genes in some genetic backgrounds, it is possible to delete either gene in other strain backgrounds, including in the BY4741 background used in this study; such rnr1⌬ and rnr4⌬ strains grow slowly and are hypersensitive to HU (Wang et al, 1997;Dubacq et al, 2004). We were therefore able to determine whether cells that lack Ccr4 have a genetic requirement for full RNR activity.…”
Section: Journal Of Cell Science 119 (24)mentioning
confidence: 99%
“…R2 houses a diferric-tyrosyl radical [(Fe) 2 -Y⅐] cofactor that is essential for catalysis. In Saccharomyces cerevisiae, there are two genes encoding R2: RNR2 (␤) and RNR4 (␤Ј) (23)(24)(25). Recent studies (26)(27)(28) have established the fact that the active form of R2 is the ␤␤Ј heterodimer (formerly designated Rnr2-Rnr4).…”
mentioning
confidence: 99%